The Feasibility Test of “COVID” Learning Strategy: An Alternative Approach to Cope Learning Process during Pandemic of COVID-19 - Sh Sugiharto; Benny Arief Setyanto (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2021)
Introduction: The COVID-19 outbreak requires spread prevention strategies that affects the education system at all levels. Consequently, appropriate and relevant learning strategies are required. The study aimed to examine the feasibility of “COVID” learning strategy as an alternative online learning system during pandemic COVID-19. Methods: The study applied a pre-experimental design with a one-group pretest-posttest approach. The sample size (34 participants) was determined using G*Power 3.1.9.7 software. The open recruitment of the participants was announced through WhatsApp. Students who were willing to be the participants were asked to fulfill the enrollment link. As the intervention, nursing students were taught using the